2022
DOI: 10.1021/acs.est.2c03524
|View full text |Cite
|
Sign up to set email alerts
|

Photo-Reactivity and Photo-Transformation of Algal Dissolved Organic Matter Unraveled by Optical Spectroscopy and High-Resolution Mass Spectrometry Analysis

Abstract: The rapid proliferation of planktonic algae induced by eutrophication and climate warming make algae dissolved organic matter (AOM) an important source of dissolved organic matter (DOM) in surface waters, but the understanding of the link between AOM composition and photo-reactivity/photo-transformation of DOM in aquatic systems is limited. Here, intracellular organic matter (IOM) from Microcystis aeruginosa was extracted and subjected to molecular weight (MW) fractionation. Results indicated that IOM had lowe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 76 publications
0
24
0
Order By: Relevance
“…The samples were left undisturbed for one week to allow the microbes in the water to reach a stable state prior to the experiments. A concentration of 5 mg/L AOM with 13 C was added to track the utilization of labile organic matter; the AOM concentration was based on the background organic matter content of the water and a previous study . A gas-permeable poly­(ether sulfone) (PES) membrane was used to cover each bottle to avoid excessive evaporation.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The samples were left undisturbed for one week to allow the microbes in the water to reach a stable state prior to the experiments. A concentration of 5 mg/L AOM with 13 C was added to track the utilization of labile organic matter; the AOM concentration was based on the background organic matter content of the water and a previous study . A gas-permeable poly­(ether sulfone) (PES) membrane was used to cover each bottle to avoid excessive evaporation.…”
Section: Methodsmentioning
confidence: 99%
“…Algal organic matter (AOM) is a crucial component of natural organic matter (NOM) that is related to eutrophication and net primary productivity (NPP). , As a freshwater phytoplankton belonging to Chlorophyta, Chlorella sp. is widely distributed in aquatic systems. , Chlorella sp.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…As a vital component in the aquatic environment, plankton play a pivotal role in the flow of energy through ecosystem nutrients and carbon cycling and provide early warning signs of risky environmental changes . Previous studies have revealed the correlations between water quality and plankton, including zooplankton and phytoplankton.…”
Section: Introductionmentioning
confidence: 99%